ANALISIS PENGARUH TINGKAT PENGANGGURAN, INDEKS KORUPSI, INDEKS NIKKEI 225, HARGA MINYAK DAN HARGA EMAS TERHADAP IHSG PERIODE 1998-2014 - Aland Budiman (Parsimonia - Jurnal Ekonomi dan Bisnis, 2015)
Causes fluctuations Composite Stock Price Index (IHSG) macroeconomic factors. The purpose of this study was to analyze the effect of the unemployment rate, corruption index, the Nikkei 225 index, price of oil, price of gold against IHSG in 1998-2014. The study used multiple linear regression to see the influence of the independent variable on the dependent. One of the requirements to perform multiple test analysis necessary to test classic assumptions. This is necessary so that the resulting regression equation is BLUE (Best, Linear, Unbiased, Estimator). Results of this study was the rate of unemployment, corruption index, and the price of oil becomes a variable that no significant positive effect on IHSG period 1998-2014. Variable Nikkei 225 index and the gold price variable positive significant effect on IHSG. Adjusted R-square results in this study showed 98.7% which may explain the effect of variable levels of unemployment, corruption index, the Nikkei 225 index, the price of oil, the price of gold against IHSG year 1998-2014